Pengaruh NPM dan DER terhadap Return Saham Perusahaan Sektor Basic Materials periode 2019-2023 - Putri, Riska Ananda; Faradila Meirisa (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the effect of Net Profit Margin (NPM) and Debt to Equity Ratio (DER) on Stock Returns in Basic Materials sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The research sample consisted of 80 companies selected using the purposive sampling method from a total population of 108 companies. Data was obtained from the annual financial statements and analyzed with the help of SPSS 25. The results of this study show that Net Profit Margin (NPM) has a negative and significant influence on Stock Returns, while Debt to Equity Ratio (DER) has a positive and significant influence. Simultaneously, these two variables affect Stock Returns. The results of this study indicate that companies need to balance profitability and capital structure to increase investment attractiveness. For investors, Net Profit Margin (NPM) and Debt to Equity Ratio (DER) can be used as the main indicators in assessing potential for growth.  Keyword: Net Profit Margin; Debt to Equity Ratio; Stock Return; Sector Basic Materials